2020
DOI: 10.1021/jacs.0c09572
|View full text |Cite
|
Sign up to set email alerts
|

Expanded N-Confused Phlorin: A Platform for a Multiply Fused Polycyclic Ring System via Oxidation within the Macrocycle

Abstract: Novel interrupted π-conjugated macrocycles derived from expanded porphyrinoids were synthesized, and their unique reactivity was investigated in this work. The specific porphyrin analogs, so-called phlorins and isoporphyrins, possess a meso-sp3 methylene moiety, showing inner 3NH and 1NH pyrrolic cores, respectively, and extended near-infrared (NIR) absorption. Expanded N-confused pentapyrrolic phlorin analog 1 bears an interrupted cyclic π-conjugated system that is featured by a distinct higher HOMO and a low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 71 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…For example, calixdicarbahexaphyrin 2 showed one reversible oxidation at 0.46 V, two quasi-reversible oxidations at 0.75 and 0.86 V, and two irreversible reductions at −1.54 and −1.90 V. The low oxidation potential values of calixdicarbahexaphyrins 2–4 revealed that these macrocycles are rich in electrons and can be easily oxidized. This is in agreement with the recent study by Xie, Furuta, and co-workers on expanded N-confused phlorins …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…For example, calixdicarbahexaphyrin 2 showed one reversible oxidation at 0.46 V, two quasi-reversible oxidations at 0.75 and 0.86 V, and two irreversible reductions at −1.54 and −1.90 V. The low oxidation potential values of calixdicarbahexaphyrins 2–4 revealed that these macrocycles are rich in electrons and can be easily oxidized. This is in agreement with the recent study by Xie, Furuta, and co-workers on expanded N-confused phlorins …”
Section: Resultssupporting
confidence: 94%
“…The electronic properties of expanded porphyrins can be altered by replacing one or more pyrrole rings with other heterocycles such as furan, thiophene, selenophene, tellurophene, pyridine, bipyridine, phenanthroline, dibenzothiophene, etc., or carbacycles such as benzene, naphthalene, biphenyl, phenanthrene, fluorene, etc. Over the years, several different varieties of expanded porphyrins have been synthesized and their physicochemical properties have been explored. , Interestingly, in most of the expanded porphyrins, one or more pyrrole/heterocycle rings prefer to remain inverted because of the flexible macrocyclic ring and the α- or β-carbon of the inverted pyrrole/heterocycle ring(s) may be involved in fusion with a N atom of the adjacent pyrrole ring to form singly or doubly fused expanded porphyrinoids. Alternately, an appropriate precursor that contains an inverted or confused pyrrole ring can be used to prepare N-confused porphyrinoids, which may exhibit fusion during the oxidation step to form fused porphyrinoids. , The literature survey revealed that several macrocycles that involve pyrrole ring inversion followed by fusion with the adjacent pyrrole N have been reported, but reports on the fusion of the pyrrole N with the carbon of the adjacent non-inverted pyrrole carbon are very scarce . Recently, we reported the synthesis of dicarbahomoporphyrins by (4+0) condensation of dicarbatetrapyrrane with aldehyde using mild acid-catalyzed conditions .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… These new species feature excellent long-wavelength absorption, enriched redox activities, and outstanding affinity toward anion (e.g., F – , AcO – ). , Although the synthesis of phlorin can date back to 1960 when Woodward employed it as an intermediate in the total synthesis of chlorophyll, the breakthrough for efficiently preparing such macrocycles took place until early 2000. Thereafter, many novel phlorin derivatives such as N-confused phlorins, core-modified phlorins, and expanded phlorins have been prepared with the aim to investigate the chemical transformations, unique photophysical properties, as well as chelating/sensing behaviors in-depth. However, the restriction of the meso-substituents (C 6 F 5, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, attachment of two non-hydrogen moieties like methyl and phenyl derivatives at the meso-sp 3 carbon has been demonstrated to be an effective way to stabilize phlorins. On this basis, inclusion of an N-confused pyrrolic unit (linked at the α and β positions) into the phlorin macrocycle may afford the so-called N-confused phlorins (Scheme ), which demonstrate intriguing photophysical and electrochemical properties as well as unprecedented chemical reactivity like regioselective oxidative ring cleavage. , …”
mentioning
confidence: 99%